2021
DOI: 10.1111/dar.13256
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the patterns of and factors associated with increased alcohol consumption since COVID‐19 in a UK sample

Abstract: Introduction To examine changes in drinking patterns and to assess factors associated with reported increases in frequency of drinking, units consumed and frequency of heavy episodic drinking (HED) during the UK lockdown. Methods Online cross‐sectional survey of 2777 self‐selected UK adults. Results Thirty percent of participants reported drinking more frequently in lockdown, 16% reported drinking more units per drinking occasion and 14% repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 31 publications
6
47
2
2
Order By: Relevance
“…Just over 40.0% of respondents reported lower alcohol consumption levels during the pandemic; this contrasts with similar studies, which have reported an increase in alcohol consumption among individuals with T2DM 10,14,15 . Additionally, research has reported an increase in alcohol consumption among the general UK population 19,20 . However, Alcohol Change UK 20 also found that one in three individuals were drinking less during lockdown, a finding similar to ours.…”
Section: Discussioncontrasting
confidence: 73%
“…Just over 40.0% of respondents reported lower alcohol consumption levels during the pandemic; this contrasts with similar studies, which have reported an increase in alcohol consumption among individuals with T2DM 10,14,15 . Additionally, research has reported an increase in alcohol consumption among the general UK population 19,20 . However, Alcohol Change UK 20 also found that one in three individuals were drinking less during lockdown, a finding similar to ours.…”
Section: Discussioncontrasting
confidence: 73%
“…These findings highlight the importance of continued public health messaging on smoking, especially as we emerge from the Covid-19 pandemic. Bidirectional changes in health behaviours associated with lockdown have also been reported in other contexts including alcohol use and vaping [ 9 , 21 , 22 ]. On this basis, it has been suggested that public health policies, measures and media are required to promote greater self-awareness, self-help, and self-care within the home setting to prevent later strains on the healthcare system [ 23 ].…”
Section: Discussionmentioning
confidence: 91%
“…However, scientific literature shows mixed results. Several studies investigating alcohol consumption during the pandemic suggest that psychological distress related to COVID-19 is linked to changes in drinking behaviors, including heavy drinking (more units per occasion) and increased frequency of consumption [ 8 , 39 , 40 , 41 , 42 ]. However, other studies reported no change in alcohol consumption or, similarly to the current study, a reduction in alcohol consumption [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%